PENGGUNAAN BUKU CERITA FABEL DENGAN MODEL QUANTUM LEARNING DALAM PEMBELAJARAN MEMBACA PERMULAAN DI SEKOLAH DASAR - Kristina E. Noya Nahak; Cornelia Amanda Naitili (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2023)
The present study investigates the low level of early reading skills among first-grade students at Oetona Public Elementary School, as evidenced by their difficulties in letter and syllable spelling as well as distinguishing letter forms. Additionally, students exhibit a lack of enthusiasm when reading sentences or short stories found in books or written by the teacher on the whiteboard. To address this issue, the utilization of Fable Storybooks with the Quantum Learning Model in early reading instruction for first-grade students at Oetona Public Elementary School was introduced, aiming to make a positive contribution to the development of students' early reading skills. The research employed a qualitative approach with a descriptive design. The findings of the study indicate that the implementation of Fable Storybooks with the Quantum Learning Model has a positive impact on students' early reading abilities. The majority of the students achieved a level of "excellent" in their early reading skills. The results and analysis demonstrate that the use of Fable Storybooks with the Quantum Learning Model contributes significantly to the improvement of students' early reading outcomes. Students displayed high enthusiasm and imagination during the learning process and demonstrated notable progress in their reading abilities